Mekanisasi Fatwa dan Ustadz Virtual: Menggugat Epsitemologi Isnad di Hadapan Algoritma Chatbot Fikih - Agung Nugroho Reformis; Wafiq Azizah; Idlofi; Maria Ulva (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2026)
This article examines the commodification and mechanization of religious authority in the digital era through the emergence of fiqh chatbots and artificial intelligence (AI)-based virtual ustadzs. The primary focus of this research is to analyze the disruption of the epistemology of isnad (traditional chain of transmission) caused by the massive, economically driven production of fictional da'wah content on social media. Employing a netnographic approach, the study traces the AI da'wah ecosystem through the Aiman Aisha chatbot (Republika), TikTok creator accounts (@nia.hajar_s and @creative_aldi), and discourse analysis of hashtags such as #kontenaiislami, #fotoaiberbicara, #dakwahai, and #ustadzai. This phenomenon is analyzed using Jean Baudrillard's theory of Simulacra and Simulation. The findings indicate that virtual ustadzs and fiqh chatbots do not merely represent religious figures; rather, they operate as the generation by models of a real without referential origin, creating a condition of hyperreality. Within this ecosystem, the simulation process substitutes the signs of the real religious authority into operational algorithms. The visuals of AI ustadzs and algorithmic fatwas essentially mask the absence of a profound reality, as there is no valid scholarly transmission (isnad) behind the mass-produced content. Instead of transmitting divine truth, the mechanization of fatwas for affiliate commissions and views triggers an implosion of meaning in the media. In conclusion, fiqh chatbot algorithms and AI ustadzs disrupt the transmission of Islamic knowledge by replacing sacred genealogy (isnad) with the purely commercial allure of digital simulacra.